Diagnostic, prognostic and predictive value of cell-free miRNAs in prostate cancer: a systematic review. Issue 1 (December 2016) - Endzeliņš, Edgars; Melne, Vita; Kalniņa, Zane; Lietuvietis, Vilnis; Riekstiņa, Una; Llorente, Alicia; Linē, Aija
Abstract Prostate cancer, the second most frequently diagnosed cancer in males worldwide, is estimated to be diagnosed in 1.1 million men per year. Introduction of PSA testing substantially improved early detection of prostate cancer, however it also led to overdiagnosis and subsequent overtreatment of patients with an indolent disease. Treatment outcome and management of prostate cancer could be improved by the development of non-invasive biomarker assays that aid in increasing the sensitivity and specificity of prostate cancer screening, help to distinguish aggressive from indolent disease and guide therapeutic decisions. Prostate cancer cells release miRNAs into the bloodstream, where they exist incorporated into ribonucleoprotein complexes or extracellular vesicles. Later, cell-free miRNAs have been found in various other biofluids. The initial RNA sequencing studies suggested that most of the circulating cell-free miRNAs in healthy individuals are derived from blood cells, while specific disease-associated miRNA signatures may appear in the circulation of patients affected with various diseases, including cancer. This raised a hope that cell-free miRNAs may serve as non-invasive biomarkers for prostate cancer. Indeed, a number of cell-free miRNAs that potentially may serve as diagnostic, prognostic or predictive biomarkers have been discovered in blood or other biofluids of prostate cancer patients and need to be validated in appropriately designed longitudinal studies and clinical trials. In this review, we systematically summarise studies investigating cell-free miRNAs in biofluids of prostate cancer patients and discuss the utility of the identified biomarkers in various clinical scenarios. Furthermore, we discuss the possible mechanisms of miRNA release into biofluids and outline the biological questions and technical challenges that have arisen from these studies.